Peluang dan Tantangan Era Baru Sistem Pemidanaan Indonesia - Mubarok, Husni; Yulianti , Yeni (Federation of Indonesian Probation Officer, 2023)
The Government of the Republic of Indonesia recently The Act No. 1 of 2023 on Criminal Code (KUHP) and the Act No. 22 of 2022 on Correctional Affairs (Correctional Law). The aim of updating or making fundamental changes to the Criminal Code is decolonization, democratization, consolidation, and harmonization of criminal law in a codified and comprehensive manner. The new Criminal Code focuses on maintaining harmony between actions/external nature as objective factors and psychology/mental attitudes as subjective factors, as well as restorative justice. The Correctional Law emphasizes the role of correctional actions of prisoners to help them realize their mistakes, not to repeat criminal offenses, and be ready to return as better and more functional people. Using a qualitative descriptive analysis method, this article discusses the readiness of Probation and Parole officers at Correctional Centers (Pembimbing Kemasyarakatan/PK Bapas) to face the opportunities and challenges in the implementation of the Criminal Code and the Correctional Law. Expansion of the duties and functions of the PK Bapas in the Restorative Justice involves the writing of Social Research of Restorative Justice report for adult suspects. Furthermore, Probation and Parole officers have to be able to carry out communication and mitigation of guidance. Urgent strategic steps need to be taken, including positive legal harmonization vertically and horizontally, competence, favourable personality, exemplary behaviour in law compliance and enforcement, law enforcement infrastructure, as well as legal support and awareness of the community. Keywords: Correctional, Correctional Law, Criminal Code, Probation and Parole Officer, Restorative Justice. Abstrak. Pemerintah Republik Indonesia baru saja mengesahkan UU RI No. 1/ 2023 tentang KUHP dan UU RI No. 22/ 2022 tentang Pemasyarakatan (UU PAS). Tujuan pembaruan atau perubahan mendasar dari KUHP adalah dekolonialisasi, demokratisasi, konsolidasi, dan harmonisasi hukum pidana secara menyeluruh dan terkodifikasi. KUHP baru terpusat pada pemeliharaan harmoni antara perbuatan/lahiriah sebagai faktor objektif dan kejiwaan/sikap mental sebagai faktor subjektif, serta keadilan restoratif. UU PAS mempertegas peran pembinaan narapidana untuk menginsyafi kesalahan dan tidak mengulangi kembali delik pidana dan siap menjadi orang yang lebih baik serta berguna. Dengan metode analis deskriptif kualitatif, tulisan ini membahas kesiapan Pembimbing Kemasyarakatan di Balai Pemasyarakatan (PK Bapas) dalam menghadapi peluang dan tantangan penerapan KUHP dan UU PAS. Perluasan tugas dan fungsi PK Bapas meliputi penyusunan Litmas Keadilan Restoratif pada tersangka dewasa. Selain itu, PK harus mampu untuk melakukan komunikasi dan mitigasi pembimbingan. Diperlukan langkah-langkah strategis yang mendesak untuk dilakukan, antara lain harmonisasi hukum positif secara vertikal dan horisontal, kompetensi, kepribadian yang baik, memberikan teladan dalam kepatuhan dan penegakan hukum, infrastruktur penegakan hukum, serta dukungan dan kesadaran hukum masyarakat.